Cyclosporine – in the Management of Severe Cutaneous Adverse Drug Reactions - Anandan, V.; Wahab , Afthab Jameela; Sundari, P. S. Mohana; Nandhini, Yoga; Rajan , Ragini (Current Overview on Disease and Health Research Vol. 2, 2022)
The aim of this study was to assess the efficacy and safety of cyclosporine in treating Severe cutaneous adverse drug reactions (sCADR). A three-year retrospective study was conducted in department of dermato-venereo-leprology at a tertiary care centre in South India. Twenty patients who met the inclusion criteria (one DRESS, ten SJS, and nine TEN patients) were chosen for the study out of the 34 in-patients who experienced adverse drug reactions (ADRs). The offending drug(s) were withheld, routine investigations were conducted, and the severity was evaluated based on SCORTEN. Fixed drug eruption and TEN with multiorgan failure were also excluded. Dexamethasone injections at a dose of 1 mg/kg per day were used to start the course of treatment. If not contraindicated, oral cyclosporine was administered at a dose of 100 mg daily for two weeks, decreased by 50 mg/week, and discontinued once the lesions had healed in those who had not responded well in three days. The average number of stabilisation days, the rate of cutaneous re-epithelialization, and the length of hospitalisation were used to evaluate cyclosporine's effectiveness. Patients stabilised more quickly with the use of cyclosporine, and re-epithelialization happened sooner; concurrent treatment with steroids assisted with the early tapering of steroid dose. The length of the hospital stay and the recovery period were reduced. There was no mortality associated with cyclosporine, and there was no apparent toxicity.